The Effectiveness of a Digital Audio Writing Podcast Based on Imla’ in Teaching Basic Arabic Nahwu - Alemsyah, Mochammad Raihan; Abdurrahman, Maman; Fuadi, Farhan; Suhendar, Zikri Kurniawan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
Learning Arabic grammar (nahwu) is often perceived by secondary school students as difficult and abstract due to its rule-based nature and the predominance of teacher-centered instructional approaches, which frequently limit student engagement and meaningful practice. This study investigates the effectiveness of an imlā’-based digital audio podcast in improving students’ mastery of basic Arabic grammar (nahwu). This study aims to examine the effectiveness of a digital audio writing podcast based on imlā’ in improving students’ mastery of basic nahwu, specifically in classifying Arabic word categories (ism, fiʿl, and ḥarf). The scope of this research focuses on evaluating learning outcomes and students’ learning experiences when using podcast-based instruction compared to conventional teaching. Using a quantitative quasi-experimental design with a non-equivalent control group, the research involved 44 tenth-grade students divided into an experimental class that used podcast media and a control class that received conventional instruction. Students completed pre- and post-tests that assessed their ability to classify Arabic word categories ism, fiʿl, and ḥarf supported by an interview questionnaire exploring their learning experience. As most datasets failed to meet normality assumptions based on the Shapiro–Wilk test, the Wilcoxon Signed Rank and Mann–Whitney U tests were employed. The findings show significant improvement in both groups; however, the experimental group demonstrated a stronger gain, increasing from a mean score of 62 to 87, compared with the control group’s increase from 71 to 85. Despite this improvement, the Mann–Whitney analysis indicated no significant difference between the two groups at pretest (p = 0.280) or posttest (p = 0.133), suggesting comparable score distributions. These findings demonstrate that imlā’-based podcast media significantly enhances students’ grammatical mastery and offers a flexible digital learning alternative. This study contributes empirically by demonstrating that integrating imlā’-based podcast media can effectively support Arabic grammar learning in digital contexts. Future research is recommended to explore long-term learning effects and apply this model to broader nahwu topics and larger sample populations.